The power of the collective empowers women: Evidence from self-help groups in India - Kumar, Neha; Raghunathan, Kalyani; Arrieta, Alejandra; Jilani, Amir Hamza; Pandey, Shinjini (Elsevier, 2021)
Women’s groups are important rural social and financial institutions in South Asia. In India, a large majority of women’s groups programs are implemented through self-help groups (SHGs). Originally designed as savings and credit groups, the role of SHGs has expanded to include creating health and nutrition awareness, improving governance, and addressing social issues related to gender- and caste-based discrimination. This paper uses panel data from 1470 rural Indian women from five states to study the impact of SHG membership on women’s empowerment in agriculture, using the project-level Women’s Empowerment in Agriculture Index (pro-WEAI) and the abbreviated Women’s Empowerment in Agriculture Index (A-WEAI). Because SHG membership was not randomized and women who self-select to be SHG members may be systematically different from non-members, we employ nearest neighbor matching methods to attribute the impact of SHG membership on women’s empowerment in agriculture and intrahousehold inequality. Our findings suggest that SHG membership has a significant positive impact on aggregate measures of women’s empowerment and reduces the gap between men’s and women’s empowerment scores. This improvement in aggregate empowerment is driven by improvements in women’s scores, not a deterioration in men’s. Greater control over income, greater decisionmaking over credit, and (somewhat mechanistically, given the treatment) greater and more active involvement in groups within the community lead to improvements in women’s scores. However, impacts on other areas of empowerment are limited. The insignificant impacts on attitudes towards domestic violence and respect within the household suggest that women’s groups alone may be insufficient to change deep-seated gender norms that disempower women. Our results have implications for the design and scale-up of women’s group-based programs in South Asia, including the possibility that involving men is needed to change gender norms.